(untitled) - Dawes, Chip (San Francisco, CA, 2002)
Here's the book you need to prepare for Exam 1Z0-007: Introduction to Oracle9i: In-depth coverage of official exam objectives Practical information on using SQL in a real-world Oracle9i en Hundreds of challenging review questions, in the book and on the CD
Keywords: Electronic data processing personnel,Quản lý cơ sở dữ liệu,Database management,Xử lý dữ liệu điện tử; Certification,Kiểm tra,Examinations